2022
DOI: 10.1055/s-0042-1750125
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Delayed Microvascular Breast Reconstruction after Radiation Therapy

Abstract: Background The purpose of this study was to determine the optimal timing of delayed microvascular breast reconstruction after completion of postmastectomy radiation therapy (PMRT). The authors evaluated whether the timing of reconstruction after PMRT completion affects the development of major postoperative complications. We hypothesize that delayed microvascular breast reconstruction can be safely performed within 12 months of PMRT completion. Methods A retrospective chart review of microvascular, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Many studies have tried to evaluate the effect of the timing of radiation therapy in relation to the timing of breast reconstruction with mixed results reported. [31][32][33] Additionally, the need for This article is protected by copyright. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have tried to evaluate the effect of the timing of radiation therapy in relation to the timing of breast reconstruction with mixed results reported. [31][32][33] Additionally, the need for This article is protected by copyright. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have tried to evaluate the effect of the timing of RT in relation to the timing of breast reconstruction with mixed results reported. [28][29][30] Additionally, the need for postoperative radiation has led many surgeons to favor the delayed-immediate approach with in an attempt to improve their aesthetic results and decrease their overall complications while getting patients into adjuvant treatment as expeditiously as possible. 31,32 There is sparse literature on the exact effects of unilateral radiation on the aesthetic outcomes of autologous breast reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the investigators found no statistical significance between timing of reconstruction after PMRT and complications, though they did find a nonsignificant increase in complications in the 2 to 6 month cohorts. 33 Additionally, at a single academic institution, Elver et al demonstrated the efficacy of early reconstruction in patients receiving radiation, reporting lower levels of wound complications in those who received reconstruction in less than 3 months, though this finding was nonsignificant as the study was underpowered ( p > 0.05). 34 Our study builds upon these findings performed across multiple institutions with statistical significance, illustrating reconstruction may be safely performed in the 0 to 3 month period after PMRT.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study, Momoh et al [ 21 ] reported that there was no significant difference in the incidence of complications between patients who underwent BR sooner than 12 months after PMRT and those who underwent BR later and came to the same conclusion regarding these patients when BR was performed sooner or later than 6 months after PMRT. A recently published retrospective study investigated 303 patients who underwent delayed microvascular BR after PMRT [ 22 ]. The patients were divided into three groups according to whether they underwent reconstruction at 0–12 months, 12–18 months, or 18–50 months after PMRT.…”
Section: Timing Of Pmrt In Patients Undergoing Brmentioning
confidence: 99%